Non-Smoker’s Cancer- Human Papilloma Virus (HPV) Induced Head & Neck Squamous Cell Carcinoma (HNSCC) - Ghoshal, Nanda Kishore; Singh, Dr. Susanchita (Medical Science Journal for Advance Research, 2024)
Head and neck squamous cell carcinoma is recognized as 6th most common cancer worldwide. Etiological factors are generally cigarettes, alcohol consumption also tobacco products such as ghutka, pan masala and betel quid also triggers the development of OSCC. Among several causes of cervical malignancies which the second most carcinoma is the world, infection with some types of human papilloma virus (HPV) is thought to be the greatest cervical cancer risk factor. Over 150 subtypes of HPV have been identified; from which more than 40 types of HPVs are typically transmitted through sexual contact and infect the anogenital region and oral cavity. HPV is suspected as the principle causative factor for oral malignancy in non smoker and non-alcoholic patients. It was also reported to be associated with Head and neck squamous cell carcinoma in 1995. The recently introduced vaccine for HPV infection is effective against certain subtypes of HPV which are associated with cervical cancer, genital warts, and some less common cancers, including oropharyngeal cancer. The value of HPV vaccination for oral cancer prevention is still controversial and hypothetical; some evidence also supports the possibility that HPV vaccination may be preventive factor in reducing the incidence of oral cancer